Is Digital Tax Bitter or Better for an Economy? Referring to a Case on Export Driven Information Communication Technology Sector in Sri Lanka - Pemerathna, A.H.S. (University of Sri Jayewardenepura, Nugegoda, 2016)
Main intention of this study was to identify the significance of digital taxation on the economy of Sri Lanka. Moreover the study has observed factors such as investment potential, government tax collectability and citizen to government responsibility; referring to the export driven Information Communication Technology of Sri Lanka. Digital taxation policies and practices in other countries including USA, UK and India were reviewed under the literature review. Inductive method was followed in the study and the qualitative data was gathered through interviews and open-ended questionnaires. Results indicate that in the export driven ICT sector tax rates are comparatively low in Sri Lanka. Further, foreign investors’ investment motives are increased as a result. Majority of the investors agreed that their investment motives are backed by a no tax environment; especially in sectors such as B2B Telecommunication, web design and development. This study reflects the existing tax policy on digital products. Further, areas of inefficiencies are highlighted indicating policy gaps in this sector. Moreover, this research contributes to the business fraternity by highlighting the benefits on tax savings in this industry.
Keywords: Government Policies; Digital Taxation; Digital Goods; Taxation Regimes; Digital Markets; Taxation Framework